Quantitative analysis of piperidin-1-ium {[5-(2-furyl)-4-phenyl-4H-1,2,4-triazol-3-yl]thio}acetate, substance of the veterinary drug «Tryfuzol», in poultry meat by LC–DAD–MS - Varynskyi, B. O.; Knysh, Ye. G.; Parchenko, V. V.; Panasenko, O. I.; Kaplaushenko, A. G.; Варинський, Борис Олександрович; Книш, Євгеній Григорович; Парченко, Володимир Володимирович; Панасенко, Олександр Іванович; Каплаушенко, Андрій Григорович; Варинский, Б. А.; Кныш, Е. Г.; et al. (Запорізький державний медичний університет, 2015)
Aim. Development of sensitive, acurate, reproducible HPLC-DMD-MS method for determination of the residual amounts of active drug substance «Tryfuzol» in poultry homogenate samples and application of this method for testing chiken groups is an important task for the conﬁrmation of this drug safety. Methods and results. The substance extraction conditions were optimized for methods development. It was established optimum extraction condition. Chromatographic conditions and mass spectrometric studies were optimized. As mobile phase, a ﬂow rate of 0.4 ml min-1 isocratic elution 0.1% (v/v) formic acid in water (A) acetonitrile containing 0.1% (v/v) formic acid (B). The composition of the mobile phase of 70% / 30% (v/v). Total running time is 5 minutes. Wavelength of the detector is 276 nm. Control of substances availability was carried by retention time and under UV and mass spectra. Conclusion. The technique complies with relevant regulations. The absence of said substance in the study chiken group was proven by using developed techniques. Розробка чутливої, правильної, відтворюваної ВЕРХ-ДМД-MС методики визначення залишкових кількостей активної субстанції препарату «Tryfuzol» у зразках гомогенату м’яса птиці та застосовування цього методу для випробувальних груп курей є важливим завданням для підтвердження безпеки використання вказаного препарату. З метою розробки методики оптимізовано умови екстракції речовини. Встановлено оптимальні умови екстракції. Оптимізовано умови хроматографічних і мас-спектрометричних досліджень. Як рухому фазу зі швидкістю потоку 0,4 мл хв-1 з ізократним елююванням використали 0,1% (об/об) форміатної кислоти у воді (А), ацетонітрил, що містить 0,1% (об/об) форміатної кислоти (B). Склад рухомий фази 70% А/30% В (об/об). Загальний час роботи становить 5 хв. Довжина хвилі детектора – 276 нм. Контроль наявності субстанції здійснили за часом утримування, а також на підставі УФ і мас-спектрів. Розроблена методика відповідає вимогам відповідних нормативних документів. Також за допомогою цієї методики доведено відсутність указаної субстанції у групі курей, що досліджували. Разработка чувствительной, правильной, воспроизводимой ВЕРХ-ДМД-MС методики определения остаточных количеств активной субстанции препарата «Tryfuzol» в образцах гомогената куриного мяса и применения этого метода для испытуемых групп кур является важной задачей для подтверждения безопасности использования указанного препарата. С целью разработки методики оптимизированы условия экстракции вещества. Установлены оптимальные условия экстракции. Оптимизированы условия хроматографических и масс-спектрометрических исследований. В качестве подвижной фазы со скоростью потока 0,4 мл мин-1 с изократическим элюированием использовалось 0,1% (об/об) формиатной кислоты в воде (А), ацетонитрил, содержащий 0,1% (об/об) формиатной кислоты (B). Состав подвижной фазы 70% A/ 30% В (об/об). Общее время хроматографирования составляет 5 мин. Длина волны детектора – 276 нм. Контроль наличия субстанции проводили по времени удерживания, а также на основании УФ и масс-спектров. Разработанная методика соответствует требованиям соответствующих нормативных документов. Также с помощью данной методики доказано отсутствие указанной субстанции в исследуемой группе кур.
Кількісне визначення піперидиній {[5-(2-фурил)-4-феніл-4H-1,2,4-триазол-3-іл] тіо}ацетату, речовини ветеринарного препарату «Трифузол», в м’ясі птиці за допомогою ВЕРХ-ДМД-МС
Количественное определение пиперидиний {[5-(2-фурил)-4-фенил-4H-1,2,4-триазол-3-ил]тио}ацетата, субстанции ветеринарного препарата «Трифузол», в мясе птицы с помощью ВЭЖХ-ДМД-МС
Keywords: Tryfuzol; Triazoles; Poultry; Chromatography; High Pressure Liquid; ESI Mass Spectrometry; трифузол; тріазоли; птиця; хроматографія; рідинна високого тиску; ESI мас-спектрометрія; триазолы; птица; хроматография; жидкостная высокого давления; ESI масс-спектрометрия